The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.18535/ijsrm/v7i3.sh03
|View full text |Cite
|
Sign up to set email alerts
|

Study on Relationship between Recruitment and Selection and Employee Performance in Technical Training Institutes in Kenya

Abstract: The purpose of the study was to establish the relationship between Recruitment and Selection and the employee performance in Technical Institutes in Kenya. Human resource is an important corporate asset and the overall performance of company depends on the way it is put to use. In order to realize company objectives, it is essential to recruit people with requisite skills, qualification and experience and while doing so Human Resource Managers need to keep present and future requirements of organization in min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
3
0
1
Order By: Relevance
“…Recruitment and selection have become an essential part of HRM of every organization and the competitive atmosphere especially for organizations in the public sector the policies of HRM are connected with overall job performance. A research study conducted by (Khalid et al 2014) reported positive and significant connection (Matolo et al 2019).…”
Section: Human Resource Management Practicesmentioning
confidence: 98%
See 1 more Smart Citation
“…Recruitment and selection have become an essential part of HRM of every organization and the competitive atmosphere especially for organizations in the public sector the policies of HRM are connected with overall job performance. A research study conducted by (Khalid et al 2014) reported positive and significant connection (Matolo et al 2019).…”
Section: Human Resource Management Practicesmentioning
confidence: 98%
“…Recruitment and selectionis one of the most critical activities of HRM which is essential for the success of any organization as it affects the efficient performance of employees and also affects performance of an organization (Khalid, Rehman & Ilyas, 2014).For every successful organizationrecruitment and selection process is essential because the right staffs sustain and enhances the performance of an organization. Also, results of a study conducted by (Matolo, Iravo, & Waititu, 2019) found that the interaction between recruitment practices and performance management practices has a positive effect on non-financial performance and eventually the financial performance of the organization. Therefore, (McCloy, Campbell, & Cudeck, 1994) suggests finding high-quality workers an effective and active recruitment policy should be implemented to attract sufficient candidates.Recruitment and selection process allows an organization to build a skilled and the competent workforce to improve the employees' performance.…”
Section: Human Resource Management Practicesmentioning
confidence: 99%
“…Retensi karyawan adalah salah satu dari beberapa elemen yang dapat meningkatkan efektivitas karyawan. Karena melibatkan interaksi dengan karyawan baik secara langsung maupun melalui kesepakatan bersama, pengaruh hubungan karyawan terhadap kinerja karyawan relatif cukup besar (Matolo et al, 2019). Hubungan karyawan yang positif menumbuhkan pekerja yang sangat berdedikasi, termotivasi, dan loyal, yang pada akhirnya meningkatkan kinerja organisasi (Nebolisa et al, 2021).…”
Section: Multistrada Arah Saranaunclassified
“…Transformational leadership, rewards and recognition, and innovative culture Several studies (e.g Matolo et al, 2019;Pawar and Ranga, 2020). have established a significant direct relationship between rewards and recognition and various positive employee and organisational outcomes, but little is known about the moderating effect of rewards and recognition Tsarenko et al (2018).…”
mentioning
confidence: 99%